Effects of Vastus Lateralis Muscle Fascicle Length on Isokinetic Muscular Strength and Physical Fitness in Collegiate Athletes - Kwang-Jin Lee; Ho-Seong Lee (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study was to examine the effects of vastus lateralis muscle fascicle length on isokinetic muscle strength and physical fitness in collegiate athletes. METHODS 32 male collegiate athletes were classified into short fascicle length group (SFG, n=16) and long fascicle length group (LFG, n=16) by ultrasonic imaging. Both groups were tested for isokinetic muscular strength (peak torque, angle of peak torque and time to peak torque) and physical fitness (20 m sprint, T-drill, reaction time, side hop, square hop, figure of 8 hop, sergeant jump and Y-balance). RESULTS LFG showed a positive effect on pennation angle (p=.001), fascicle length (p=.001), angle of peak torque at 180°/sec (p=.037), time to peak torque at 90°/sec and 180°/sec (p=.036; p=.039), 20 m sprint (p=.016), T-drill (p=.005), side hop (p=.001) and square hop (p=.001), respectively compared to SFG. However, there was no difference between both groups of peak torque at 30°/sec, 90°/sec and 180°/sec, angle of peak torque at 30°/sec and 90°/sec, time to peak torque at 30°/sec, reaction time, sergeant jump and Y-balance. CONCLUSIONS These results found that long fascicle length of vastus lateralis muscle have excellent isokinetic muscle strength and physical fitness in collegiate athletes.